Cardiopulmonary resuscitation in quaternary neonatal intensive care units: a multicenter study. (February 2021) - Ali, Noorjahan; Lam, Teresa; Gray, Megan M.; Clausen, David; Riley, Melissa; Grover, Theresa R.; Sawyer, Taylor
Abstract: Background: The reported incidence of cardiopulmonary resuscitation (CPR) in quaternary NICU is approximately 10-times higher than in the delivery room. However, the etiologies and outcomes of CPR in quaternary NICUs are poorly understood. We hypothesized that demographic characteristics, diagnoses, interventions, and arrest etiologies would be associated with survival to discharge after CPR. Methods: Multicenter retrospective cohort study of four quaternary NICUs over six years (2011–2016). Demographics, resuscitation event data, and post-arrest outcomes were analyzed. The primary outcome was survival to discharge. Results: Of 17, 358 patients admitted to four NICUs, 200 (1.1%) experienced a CPR event, and 45.5% of those survived to discharge. Acute respiratory compromise leading to cardiopulmonary arrest occurred in 182 (91%) of the CPR events. Most neonates requiring CPR were on mechanical ventilation (79%) and had central venous access (90%) at the time of arrest. Treatments at the time of the arrest associated with decreased survival to discharge included mechanical ventilation, antibiotics, or vasopressor therapy (p < 0.01). Etiologies of arrest associated with decreased survival to discharge included multisystem organ failure, septic shock, and pneumothorax (p < 0.05). Longer duration of CPR was associated with decreased survival to discharge. The odds of surviving to discharge decreased for infants who had a primarily cardiac arrest and for infants who received epinephrine during the arrest. Conclusion: Approximately 1% of neonates admitted to quaternary NICUs require CPR. The most common etiology of arrest is acute respiratory compromise on a ventilator. CPR events with respiratory etiology have a favorable outcome as compared to non-respiratory causes.